Discipline and Inclusively Repress: The Hybrid Governance of Housing First Tenants. Issue 4 (8th August 2022) - Grainger, Garrett L.
ABSTRACT: Housing First is a popular model of homeless services that has transformed urban governance across the globe. Scholars have praised Housing First as voluntary care or criticized it as a disciplinary intervention. Both perspectives offer a partial account of Housing First case management. I extend those studies with interview-based research that conceptualizes U.S. Housing First as a hybrid form of homeless governance that exercises control through discipline and inclusive repression. Government authorities contract Housing First providers to reduce public expenditures by rehousing chronically homeless people. Case managers make disciplinary interventions until tenants are confronted with an eviction. At that point, service providers use inclusionary repression to sustain market exchanges by selectively disenfranchising tenants and rendering them pliable to disciplinary interventions in the future. This paper advances homeless scholarship by showing how, as a publicly subsidized property management service, U.S. Housing First buttresses urban housing markets through hybrid governance.